1997
DOI: 10.1074/jbc.272.33.20515
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of Functional Voltage-gated Chloride Channels from Complementary Fragments of CLC-1

Abstract: We investigated the effect of truncations on the human muscle chloride channel CLC-1 and studied the functional complementation from partial proteins. Almost complete deletion of the cytoplasmic amino terminus did not affect currents, but truncating the intracellular COOH terminus after Leu 720 abolished function. Currents were restored by coexpressing this membraneembedded part with the lacking cytoplasmic fragment that contains domain D13, the second of the two conserved cystathionine ␤-synthase (CBS) motifs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
69
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 41 publications
7
69
0
1
Order By: Relevance
“…Although the physiological role of CBS domains is still unknown, truncations removing parts of the distal CBS domain of ClC channels abolished functional expression in heterologous systems (20,36).…”
Section: Discussionmentioning
confidence: 99%
“…Although the physiological role of CBS domains is still unknown, truncations removing parts of the distal CBS domain of ClC channels abolished functional expression in heterologous systems (20,36).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it had been shown that truncating ClC-1 after CBS1 does not give rise to any current (39). In the latest work, Estévez and co-workers (12) used co-immunoprecipitation, electrophysiology, and surface-expression measurements using an extracellular epitope to show that both CBS domains are needed for the rescue of function and localization of the separately expressed NH 2 -terminal half of the channel.…”
Section: Physiology • Volume 19 • October 2004 • Wwwphysiologyonlinementioning
confidence: 99%
“…Proteins reconstituted from fragments produced by limited proteolytic cleavage or genetic methods have been studied under both in vivo and in vitro conditions [9][10][11][12][13]. Successful reconstitution implies that the internal complementarity must be highly self-selective to overcome competing interactions with other protein sequences [14].…”
Section: Introductionmentioning
confidence: 99%